2017
DOI: 10.1093/jee/tox292
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila suzukii (Diptera: Drosophilidae) Contributes to the Development of Sour Rot in Grape

Abstract: This research aimed to more clearly describe the interactions of Drosophila suzukii (Matsumura; Diptera: Drosophilidae) with microorganisms that may contribute to spoilage or quality loss of wine grapes during harvest. Experiments were conducted in controlled laboratory experiments and under field conditions to determine these effects. Laboratory trials determined the role of insect contact and oviposition to vector spoilage bacteria onto wine grapes. In the field, the roles of key organoleptic parameters in g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
55
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 31 publications
2
55
0
1
Order By: Relevance
“…With the exception of Hawaii, D. suzukii has caused economic losses throughout its introduced range. There is zero tolerance for larval infestation in harvested fruit, and in grapes, egg laying alone may result in increased disease incidence (Ioriatti et al 2018). Assuming 20% yield loss, revenue losses to D. suzukii in strawberries, blueberries, raspberries, blackberries, and cherries in California, Oregon, and Washington alone have been estimated at $511 million annually (Bolda et al 2010, Walsh et al 2011.…”
mentioning
confidence: 99%
“…With the exception of Hawaii, D. suzukii has caused economic losses throughout its introduced range. There is zero tolerance for larval infestation in harvested fruit, and in grapes, egg laying alone may result in increased disease incidence (Ioriatti et al 2018). Assuming 20% yield loss, revenue losses to D. suzukii in strawberries, blueberries, raspberries, blackberries, and cherries in California, Oregon, and Washington alone have been estimated at $511 million annually (Bolda et al 2010, Walsh et al 2011.…”
mentioning
confidence: 99%
“…has a microbial contribution as vector for the microorganisms involved in sour rot development (Barata, Santos, et al, ). Previous studies even showed that this transfer can take place without egg‐laying solely through contact (Ioriatti et al, ). However, our findings from 2017 showed that the flies are not only crawling over the berry surface, spreading the agents involved in sour rot, but additionally were able to oviposit, develop through larval stages and emerge as adults (Figure ).…”
Section: Discussionmentioning
confidence: 96%
“…contributing to sour rot development are proposed. First, the flies are able to vector the yeasts and bacteria associated with the disease (Barata, Santos, et al, ; Ioriatti et al, ). More importantly, a recent study with axenic flies demonstrated that flies also play a non‐microbial role, presumably through the developing larvae, which themselves trigger the decomposition of berries and thereby reinforce sour rot development (Hall, Loeb, Cadle‐Davidson, et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the fruit damage caused by the developing D. suzukii larvae, oviposition wounds make attacked fruits more susceptible to later infestations by other insects and pathogenic microorganisms (Hamby, Hernandez, Boundy‐Mills, & Zalom, ; Ioriatti et al., ; Rombaut et al., ; Swett, Carignan, Hamby, & Koivunen, ). Consequently, the small‐fruit industry and the market have a zero tolerance to D. suzukii infestation (Bruck et al., ; Haye et al., ).…”
Section: Introductionmentioning
confidence: 99%